Effects of physical training on myocardial ischaemia in patients with coronary artery disease. - Raffo, J A (1980)
The effects of a simple physical training programme were investigated in a prospective and randomised trial in patients with stable angina pectoris using a modified exercise test. Twenty-four patients with ischaemic heart disease and an ischaemic response to conventional exercise electrocardiography were randomised into two groups: 12 patients took part in a training programme and 12 patients were allocated to a control group (no training). Exercise testing was performed sequentially at entry to the study and six months afterwards. At both studies we determined the heart rate at the same level of ischaemic ST segment depression (HR/ST threshold), the duration of the test, and relation of heart rate to the exercise load. The HR/ST threshold increased only in patients who underwent the exercise programme, suggesting indirectly that training resulted in the ability to do more work and attain a higher degree of myocardial oxygen consumption at the same level of myocardial ischaemia. In addition, training led to an increase in the duration of the test and to a reduction in heart rate at any level of submaximal exercise load. It is concluded that physical training in anginal patients results in an enhancement of myocardial oxygen availability.